2014
DOI: 10.1007/s00277-014-2127-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated reticulocyte parameters for hereditary spherocytosis screening

Abstract: The laboratory diagnosis of hereditary spherocytosis (HS) is based on several screening and confirmatory tests; our algorithm includes clinical features, red blood cell morphology analysis and cryohaemolysis test, and, in case of positive screening, sodium dodecyl sulphate polyacrylamide gel electrophoresis as a diagnostic test. Using the UniCel DxH800 (Beckman Coulter) haematology analyser, we investigated automated reticulocyte parameters as HS screening tool, i.e. mean reticulocyte volume (MRV), immature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
27
0
2
Order By: Relevance
“…Hemolytic anemia is a hyperproliferative anemia, characterized by increased peripheral blood reticulocytes and the appearance of various numbers of nucleated red blood cells. HS is characterized by a high Ret value with no increase in IRF, as reported by Lazarova et al However, this characteristic has a lower diagnostic sensitivity and specificity than MSCV‐MCV < 0, MRV, or MCHC.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hemolytic anemia is a hyperproliferative anemia, characterized by increased peripheral blood reticulocytes and the appearance of various numbers of nucleated red blood cells. HS is characterized by a high Ret value with no increase in IRF, as reported by Lazarova et al However, this characteristic has a lower diagnostic sensitivity and specificity than MSCV‐MCV < 0, MRV, or MCHC.…”
Section: Discussionmentioning
confidence: 58%
“…Da Costa et al compared the membrane surface area of reticulocytes and mature erythrocytes and found that membrane vesiculation and membrane loss occurred at the reticulocyte stage in patients with HS, resulting in greatly reduced membrane surface area and MRV. Lazarova et al . examined blood cell parameters including MRV, MSCV, and IRF in 48 patients with HS, seven with AIHA, and 31 with other types of anemia and provided the first evidence for MRV as a valuable screening parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lazarova et al . investigated MRV, MSCV, and immature reticulocyte fraction in 48 cases of HS, seven cases of AIHA, and 31 cases of other types of anemia; they reported that MRV could be used to screen HS. When the MRV was <96.7 fL, the sensitivity and specificity for diagnosing HS were 100% and 88%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Для случаев НС с яркой клинической картиной соотношение RET/IRF составля-ет > 19. Выявлены статистически значимые различия в значениях показателя RET/IRF между группами паци-ентов с НС, гемолитическими анемиями, микроцити-ческими анемиями, пациентами без гематологических нарушений [16]. В нашем исследовании для всех случаев наследственного сфероцитоза показатель RET/IRF при-нимал значения более 19,5.…”
Section: Discussionunclassified